The Emergence of Determiners in French L2 from the Point of View of L1/L2 Comparison - Marzena Watorek; Pascale Trévisiol; Rebekah Rast (Languages, 2021)
The acquisition of determiners in French presents a significant challenge for both children in L1 and adults in L2. Research in L1 acquisition has found that French determiners, which are highly constrained, appear quite early relative to other languages. Using the conversational data of two beginning learners of French—a native speaker of Spanish and a native speaker of Arabic—in a natural setting (comparable to the L1 data), the present study seeks to understand how these constraints affect the acquisition of the determiner system in L2 French. Analyses reveal the following: (1) Unlike French children who produce “fillers” without clear functional distinctions, adults produce idiosyncratic pre-nominal monosyllables that not only fulfil the obligatory position of “determiner” but are also characterized by identifiable functions in terms of definiteness or indefiniteness. (2) Adult learners’ L1s (Spanish and Arabic) influence the acquisition of NP in French L2, as observed in the emergence of determination in the two learners’ productions. (3) Adult learners’ productions provide evidence of shared “language-neutral” processes attested in initial acquisition in a natural setting; these are independent of the L1 and L2 input properties.